2012
DOI: 10.4132/koreanjpathol.2012.46.4.387
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Adenocarcinomas Arising within a Gastric Inverted Hyperplastic Polyp

Abstract: We present herein the occurrence of multifocal adenocarcinomas with a minute signet ring cell carcinoma that arose within a gastric inverted hyperplastic polyp (IHP) in a 40-year-old woman. Endoscopic ultrasonography demonstrated a heterogeneous hypoechoic mass in the third layer of the gastric wall. The endoscopic submucosal dissection specimen measuring 3.5×3.2×1.8 cm was a well-circumscribed protruding lesion that had a slit-shaped cavity. Histologically, the lesion consisted mainly of endophytic proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 12 publications
0
31
3
Order By: Relevance
“…A similar lesion was recently called an IHP in other reports (2,7,8). Although several gastric IHPs accompanied by adenocarcinoma have been reported recently, histopathological criteria have not been established for these submucosal lesions, including hamartomatous polyps, hamarto- (2,7,8,10), although the pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar lesion was recently called an IHP in other reports (2,7,8). Although several gastric IHPs accompanied by adenocarcinoma have been reported recently, histopathological criteria have not been established for these submucosal lesions, including hamartomatous polyps, hamarto- (2,7,8,10), although the pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although several gastric IHPs accompanied by adenocarcinoma have been reported recently, histopathological criteria have not been established for these submucosal lesions, including hamartomatous polyps, hamarto- (2,7,8,10), although the pathogenesis remains unclear. Yamashita et al (2) suggested that IHP may be gastritis cystica profunda (GCP) associated with exaggerated hyperplastic and metaplastic changes, and they showed that two out of their four patients with IHP had coexisting GCP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations